Measuring Competition in the Banking Sector of Pakistan: An Application of Boone Indicator - Khan, Mahmood ul Hasan; Hanif, Muhammad Nadim (JISR management and social sciences & economics, 2017)
The banking sector of Pakistan has witnessed a notable transformation in its structure and business activities following the implementation of financial sector reforms since the early 1990s. Specifically, the reforms helped transform a repressed financial sector into a market oriented and sound financial sector, predominantly owned and managed by the private sector. How these developments have impacted competition among the banks is still an open question. This study attempts to answer this question with the application of a recent approach to measure competition: Boone indicator of competitiveness. This measure postulates that inefficient firms (banks) in a competitive environment are punished harshly, and there is an output reallocation from inefficient to efficient firms/banks. We have estimated elasticity of market share to marginal costs for 24 banks in Pakistan, using a balanced panel of bank level (annual) data for the year 1996 to 2015. Marginal costs are obtained indirectly by first estimating a translog cost function using earning assets as an output, and cost of financial capital, physical capital and labor as inputs. The estimated Boone Indicator value of negative 0.31 is significant and suggests that inefficient banks have been losing their market share to efficient banks over the estimation period: a reflection of underlying competitive environment. Increasing value of Boone indicator (in absolute terms) over the period of study suggests that competition among the banks in Pakistan has increased over time.